Integrated Efficacy to Effectiveness Trials. Issue 2 (19th November 2013) - Califf, R M
<x xml:space="preserve">Abstract</x> Experts in clinical research, therapeutic development, and comparative effectiveness are continually frustrated in their attempts to fit the square peg of therapeutic development into the round hole of clinical trials. Trials can be optimized to provide signals in highly controlled experiments or to estimate an intervention's effect in poorly controlled real‐world settings, but not both simultaneously. Selker and colleagues propose a continuum that creates a smooth transition from controlled experiments to real‐world, real‐time studies within a single mechanism. Clinical Pharmacology & Therapeutics (2014); 95 2, 131–133. doi:10.1038/clpt.2013.232